Frequency of BK virus genotypes in patients with colorectal cancer - Mahsa Javadi; Gholamabbas Kaydani; Roya Pirmoradi; Abdolhassan Talaiezadeh; Azadeh Haghi Navand; Mohammad Karimi Baba Ahmadi; Manoochehr Makvandi (Iranian Journal of Microbiology)
Background and Objectives: BK polyomavirus infection is prevalent and primarily asymptomatic, except for complications in kidney transplant recipients. Furthermore, its involvement in a tumorigenic family necessitates consideration in various malignancies such as urogenital tumors, prostate cancer, colorectal cancer (CRC), and brain cancer. Materials and Methods: This investigation encompassed 50 specimens of colorectal adenocarcinoma tumors, 50 adjacent tissues, and 40 urine samples, with patients having a mean age of 61 years ± 12.4 years. The detection of BK virus DNA VP1 gene and genotyping were carried out through nested-PCR and sequencing techniques. Results: Through the utilization of nested-PCR, BK virus DNA was identified in 15/50 (30%) colorectal tumor samples and 3/50 (6%) adjacent tissues (p-value = 0.008). Additionally, 6/40 (15%) urine samples exhibited positive results for BK virus DNA. Notably, among these findings, 9/15 BK virus positive tumor tissues (60%) and 3/6 BK virus positive urine samples (50%) were confirmed to be positive for BK virus subtype 4 (p-value < 0.001), whereas 2 tumor samples and 3 urine samples were attributed to BK virus type 1b2. Conclusion: It is imperative to enhance one's understanding of the etiological and risk factors pertaining to cancers. The present findings offer substantiation of a potential correlation between BK virus infection and colorectal cancer. BK virus genotype 4 was found to be dominant among the CRC patients in this study.